VALUE IN EXECUTING TUMBILO TOHE (PAIRS OF LIGHTS) EACH END OF RAMADAN AS ONE MANIFESTATION OF THE PRACTICE OF PANCASILA BY PEOPLE OF GORONTALO - Jasin, Johan (Journal of Humanity, 2015)
The prevalence of implementation tumbilo tohe (pairs of lights) by the people of Indonesia at the end of the month of Ramadan, is a cultural heritage which is formed in the Pancasila. This practice was based on: (1) religious zeal that has been imprinted in the soul of citizens, (2) a mix of custom and Islamic teachings (3) the agreement of the leader. This practice was intended to: (1) graced the month of Ramadan, (2) motivating the public to improve understanding of the teachings of Islam, (3) preserve culture (4) enhance the spirit of mutual help, please, and (5) promote the spirit of hard work and creativity. Foundation and purpose of existence value reflects tohe tumbilo Pancasila especially value: 1). the Godhead (spirituality), 2). Humanity (help help), 3). Unity (interaction and hospitality), 4). Democracy is visible from a range of model arks (5) justice is visible from the spirit of hard work preparing the implementation of the community tumbilo tohe. This is one of the culture values of the practice of Pancasila by society of Gorontalo. Globalization tumbilo tohe even modified as an instrument of regional increases in revenue through optimization of tourism sector.Â Â